KONTRIBUSI PRODUK SUSU TERHADAP ASUPAN KALSIUM PADA MAHASISWI - Triyanti, Triyanti; Aini, Wita Nurul; Sartika, Ratu Ayu Dewi (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Calcium is one of important mineral for female student to obtain the peak bone mass.This study aims to find out how the amount and adequacy of calcium intake, and the contribution of dairy products to calcium intake among female student. This study used a cross-sectional study design. A total 58 third and fourth level nutrition student were selected randomly as samples.Calcium intake is obtained by using semiquantitative FFQ that has been validated. The results of the study showed an average calcium intake was 630±395 mg/day, with 417.8±367.7 mg coming from dairy products.There was 13% student who obtained Requirement Daily Allowance for calcium. Keywords: calcium intake, dairy products, female student